2019
DOI: 10.1159/000502280
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <b><i>Cynara scolymus</i></b> on Blood Pressure and BMI in Hypertensive Patients: A Randomized, Double-Blind, Placebo-Controlled, Clinical Trial

Abstract: Background: Recent studies have suggested that artichoke (Cynara scolymus L.) may reduce certain biochemical blood factors but the efficacy of this plant on blood pressure (BP) has not yet been investigated. In this study, we determined the clinical efficacy of C. scolymuson BP and body mass index (BMI) in hypertensive patients as an adjunctive to captopril for the first time. Methods: The total phenolic content and gas chromatography-mass spectrometry metabolite profiling in leaves of C. scolymus have been ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…On another interesting note, Tropea found that GSEP was not capable of altering vascular reactivity but capable of improving the relaxation of vascular endothelial-dependent in eNOS mice's mesenteric and uterine arteries [109]. In an attempt to explore the impact of 500 mg of Cynara Scolymus L, twice daily for eight weeks on blood pressure (BP), Ardalani et al [110] looked to evaluate the clinical efficacy of C.scolymus on BP and body mass index (BMI) in patients suffering from hypertension. Interestingly, it was reported that the consumption of C.scolymus powder, which had enough flavonoid and antioxidants, despite reducing BMI, could not improve SBP and DBP.…”
Section: Antioxidant and Physical Activity Therapies For Heart Disease Related To Oxidative Stressmentioning
confidence: 99%
“…On another interesting note, Tropea found that GSEP was not capable of altering vascular reactivity but capable of improving the relaxation of vascular endothelial-dependent in eNOS mice's mesenteric and uterine arteries [109]. In an attempt to explore the impact of 500 mg of Cynara Scolymus L, twice daily for eight weeks on blood pressure (BP), Ardalani et al [110] looked to evaluate the clinical efficacy of C.scolymus on BP and body mass index (BMI) in patients suffering from hypertension. Interestingly, it was reported that the consumption of C.scolymus powder, which had enough flavonoid and antioxidants, despite reducing BMI, could not improve SBP and DBP.…”
Section: Antioxidant and Physical Activity Therapies For Heart Disease Related To Oxidative Stressmentioning
confidence: 99%
“…In several clinical trials, reductions in cholesterol levels were found but more studies are needed [ 63 , 64 , 65 , 66 ]. In addition, improved hypertension, body mass index, cardio-metabolic parameters, and hepato-protective effects have been observed [ 67 , 68 , 69 ]. Artichoke extract may be relevant as a therapeutic factor for atherosclerosis due to it lowering the rates of low-density-lipoprotein cholesterol and by its antioxidant, anti-inflammatory, and nitric oxide regulation effects [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…5. It is well-established that tannins cause a decrease in feed intake, growth rate, feed efficiency, and protein digestibility, resulting in increased excretion of proteins and essential amino acids followed by a decrease of the body mass index [152][153][154]. In a study by Venkataiah et al, tannins in the root of A. ilicifolius were shown to significantly decrease the blood glucose level in diabetic rats when orally administering 200 mg/kg of the extract for two weeks [21].…”
Section: Tanninsmentioning
confidence: 99%